Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/1010428317719275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-frequency low-intensity ultrasound with microbubbles on prostate cancer hypoxia

Abstract: Angiogenesis plays an important role in tumor growth, invasiveness, and metastasis. It is well established that prostate cancer is exposed to fluctuating oxygen tensions and both acute and chronic hypoxia exist, and these conditions can upregulate angiogenesis-associated proteins such as hypoxia-inducible factor 1 alpha and vascular endothelial growth factor A. Low-frequency low-intensity ultrasound with microbubbles can induce obvious microvessel damage in tumors, cause cell necrosis or apoptosis. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…These two cell lines are useful in vitro models for the study of endothelial functions, such as angiogenesis. Studies have reported that low-intensity ultrasound with microbubbles induces the evident microvascular damage in tumors, mainly due to inertial cavitation, which can cause cell necrosis or apoptosis (26,27). Acoustic cavitation can lead to mechanical damage of small blood vessels due to the expansion and collapse caused by oscillation of the microbubbles (28).…”
Section: Discussionmentioning
confidence: 99%
“…These two cell lines are useful in vitro models for the study of endothelial functions, such as angiogenesis. Studies have reported that low-intensity ultrasound with microbubbles induces the evident microvascular damage in tumors, mainly due to inertial cavitation, which can cause cell necrosis or apoptosis (26,27). Acoustic cavitation can lead to mechanical damage of small blood vessels due to the expansion and collapse caused by oscillation of the microbubbles (28).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that low-frequency ultrasound combined with microbubbles can promote apoptosis of prostate cancer cells, liver cancer cells, ovarian cancer cells, glioma cells, and human leukemia cells (Lagneaux et al, 2002;Bai et al, 2016;Gangeh et al, 2016), and reduce damage to normal tissues. Hou et al (2017) reported that low-frequency ultrasound combined with microbubbles can affect the hypoxic response of a tumor, inhibit tumor growth, and promote cell apoptosis. Shen YY et al (2017) reported that low-frequency ultrasound combined with microbubbles enhanced delivery of paclitaxel liposomes treating nude mice bearing intracranial glioblastoma xenografts.…”
Section: Inducing Autophagy and Apoptosis Of Tumor Cells Inhibiting mentioning
confidence: 99%
“…Many studies utilized the blood vessel destructing properties of microbubbles and ultrasound in the treatment of prostate cancer. One remarkable study explored the effect of low-frequency low-intensity ultrasound with microbubble on the hypoxia environment of prostate cancer [ 10 ]. Another noteworthy study analyzed the role of UDP glycosyltransferase 8 (UGT8) in the responses of prostate tumor to ultrasound-stimulated microbubble radiation enhancement therapy [ 11 ].…”
Section: Reviewmentioning
confidence: 99%